Research Progress in Skin Aging, Metabolism, and Related Products - Xin He; Xinyu Gao; Weidong Xie (2023)
In recent years, skin aging has received increasing attention. Many factors affect skin aging, and research has shown that metabolism plays a vital role in skin aging, but there needs to be a more systematic review. This article reviews the interaction between skin metabolism and aging from the perspectives of glucose, protein, and lipid metabolism and explores relevant strategies for skin metabolism regulation. We found that skin aging affects the metabolism of three major substances, which are glucose, protein, and lipids, and the metabolism of the three major substances in the skin also affects the process of skin aging. Some drugs or compounds can regulate the metabolic disorders mentioned above to exert anti-aging effects. Currently, there are a variety of products, but most of them focus on improving skin collagen levels. Skin aging is closely related to metabolism, and they interact with each other. Regulating specific metabolic disorders in the skin is an important anti-aging strategy. Research and development have focused on improving collagen levels, while the regulation of other skin glycosylation and lipid disorders including key membrane or cytoskeleton proteins is relatively rare. Further research and development are expected.